2021
DOI: 10.3389/fmars.2021.751401
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Feeding Characteristics and Digestion Physiology of Haliotis discus hannai and Haliotis gigantea

Abstract: Abalone (Haliotis spp.) are typical nocturnal creatures but Haliotis discus hannai is bold and active in the nighttime whereas H. gigantea tends to be timid and inactive. In this study, we quantified and compared differences in movement, feeding, and digestive physiology between H. discus hannai and H. gigantea as well as the potential molecular mechanisms on the basis of video observations and expression levels of genes related to feeding regulation. The feeding behaviors of both species were characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…The results of the cosine analysis suggested that the melatonin content and expression levels of AANAT and ASMT in the 12L:12D and 24L:00 groups exhibited a significant cosine diurnal rhythm and tended to be “higher during the day and lower during the night”, suggesting that abalones maintain their diurnal rhythm regardless of changes in the light cycle. Even though H. gigantea tends to be more shy and less active than H. discus hannai , the feeding behaviors of the two species show significant diurnal rhythms, with feeding peaks at ZT12 (00:00) [46] , further demonstrating that light is one of the external environmental factors most likely to impact the timing of biological rhythms. In the course of the experiment, food was provided at 17:00 pm every day.…”
Section: Discussionmentioning
confidence: 97%
“…The results of the cosine analysis suggested that the melatonin content and expression levels of AANAT and ASMT in the 12L:12D and 24L:00 groups exhibited a significant cosine diurnal rhythm and tended to be “higher during the day and lower during the night”, suggesting that abalones maintain their diurnal rhythm regardless of changes in the light cycle. Even though H. gigantea tends to be more shy and less active than H. discus hannai , the feeding behaviors of the two species show significant diurnal rhythms, with feeding peaks at ZT12 (00:00) [46] , further demonstrating that light is one of the external environmental factors most likely to impact the timing of biological rhythms. In the course of the experiment, food was provided at 17:00 pm every day.…”
Section: Discussionmentioning
confidence: 97%
“…discus hannai and ‘shy’ H . gigantea were significantly different 92 . With both feeding peaks appearing at 00:00, H .…”
Section: Development Trend: Construction Of Land‐based Ras Based On A...mentioning
confidence: 88%
“…91 Lyu et al found that the movement and feeding behaviours of 'lively' H. discus hannai and 'shy' H. gigantea were significantly different. 92 With both feeding peaks appearing at 00:00, H. gigantea would spend 94.6% of movement time feeding, while the feeding time of H. discus hannai only accounted for 56.0% of its cumulative movement duration. The maximum value of the alginate lyase activity of H. discus hannai and that of the expression levels of the feeding-related receptor (NPYR) appeared at 16:00.…”
Section: Selection Of Feeding Strategies Depending On Movement and Fe...mentioning
confidence: 97%
“…Increasing the success of stock enhancement requires assessments of how well the hatchery-bred individuals adapt to wild conditions. In particular, abalones are a group of typical nocturnal animals that stay away from light and hide in dark areas in the daytime, with a feeding peak at the night (Lyu et al, 2021). Olfaction cues are widely used by aquatic gastropods to detect and avoid predators, as well as to search for food (Manriquez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%